Towards an epistemology of management and economics in the Zimbabwean music industry - Mhiripiri, Joyce Tsitsi (Intellect, 2021)
This article examines the management, economics and political economy aspects of the Zimbabwe music industry. It compares management and policy practices in South Africa with those in Zimbabwe and identifies gaps that need to be filled in developing an epistemology of management and economics in the Zimbabwe music industry. Some of the issues identified include the importance of strategy – especially an industry strategy – in developing music business, the interaction between majors and indies, the significance of intellectual property rights (IPRs) for this industry, the role of government policy in nurturing a vibrant music industry and the role of stardom in creating a sustainable competitive advantage for musicians. A number of weaknesses in the Zimbabwe music industry were identified such as lack of an industry strategy, lack of coherent statistics on the music industry and a need to develop the organizational infrastructure of industry associations. The article concludes by urging researchers to complement the basic business disciplines with critical political economy, sociology of creative labour industries and cultural studies in order to produce work that focuses on the musicians as primary producers and attempts to improve their position in society